Ablation Outcomes and Predictors of Mortality Following Catheter Ablation for Ventricular Tachycardia: Data From the German Multicenter Ablation Registry. Issue 6 (23rd March 2018) - Tilz, Roland Richard; Lin, Tina; Eckardt, Lars; Deneke, Thomas; Andresen, Dietrich; Wieneke, Heinrich; Brachmann, Johannes; Kääb, Stefan; Chun, K. R. Julian; Münkler, Paula; Lewalter, Thorsten; Hochadel, Matthias; et al.
Abstract : Background: Ventricular tachycardia (VT) causes significant morbidity and mortality. Implantable cardioverter‐defibrillator shocks terminate VT but confer a significant morbidity and mortality risk. Therefore, VT ablation is increasingly common. Patients with structural heart disease (SHD) and patients with structurally normal hearts as well as the subgroup with and without ischemic heart disease were assessed for predictors of mortality and nonfatal VT recurrence. We present the first multicenter, prospective German VT registry. Methods and Results: In 334 patients, 118 structurally normal hearts and 216 SHD (74.5% ischemic heart disease), referred for VT ablation in 38 centers, long‐term follow‐up was assessed for a minimum of 12 months and analyzed for factors predicting VT recurrence rates and mortality. The VTs in SHD patients were more frequently hemodynamically unstable (34.7% versus 12.7%, P <0.0001) or incessant (9.7% versus 2.7%, P <0.05). More SHD patients underwent substrate modification than patients with structurally normal hearts who had more focal ablations. Ablation failure was 9% in both groups. Two‐year mortality was higher in patients with SHD (18.7% versus 3.5%, P <0.001). Predictors of mortality include age >60 years, incessant VT, left ventricular ejection fraction ≤30%, procedural failure, and Class I and III anti‐arrhythmic drug use at discharge. Only procedural failure is a predictor of nonfatal VT recurrence. Conclusions: Procedural failure was the sole independent predictor for nonfatal VT recurrence for our study cohort. This emphasizes the importance of a successful ablation procedure in experienced hands to reduce long‐term mortality and nonfatal VT recurrence.